If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xy + -1xz = b + -1c Solving xy + -1xz = b + -1c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Reorder the terms: -1b + c + xy + -1xz = b + -1c + -1b + c Reorder the terms: -1b + c + xy + -1xz = b + -1b + -1c + c Combine like terms: b + -1b = 0 -1b + c + xy + -1xz = 0 + -1c + c -1b + c + xy + -1xz = -1c + c Combine like terms: -1c + c = 0 -1b + c + xy + -1xz = 0 The solution to this equation could not be determined.
| -5.6x-14.3= | | -9x+13=-27 | | x-8=4-2(3x+5) | | 3d+8=6d-2 | | n+1=-17-10n-2+9n | | xy-zy=b-c | | -n-24=5-q | | 8x+38=3(x+1) | | xy-zy=b | | 2t^3-10t=t^2 | | 15-3x=15-3x | | 7x-6-4x=2x+6 | | 10-15x=35 | | 46-7x=12+10x | | 0.3333333333333333= | | 3xy+yx= | | 3x-4=6x-1 | | ax+bc+3=-6 | | -129=6(1-4n)-3n | | -(5w+u)+3(3u+5w)= | | 4z-5=19 | | 4x=4x+7 | | -4+5k=11 | | 3x^3+5x-8=0 | | (6-5s)(2-s)= | | 7+10r=77 | | 24+13=24+15 | | -30=2(w+5)-6w | | 2x+y-z=10 | | log[2](7x+2)=6 | | 2=f/ | | 10.5=x+5.5 |